Returning Home: Reconnecting with Our Childhoods - Burger, Jerry M. (Rowman & Littlefield Publishers, 2011)
Each year millions of American adults visit a childhood home. Few can anticipate the effect it will have on them. Often serving several important psychological needs, these trips are not intended as visits with people from their past. Rather, those returning to their homes have a strong desire to visit the places that comprised the landscape of their childhood. Approximately one third of American adults over the age of thirty have visited a childhood home. This book describes some of their experiences and the psychology behind the journeys. Most people who visit a childhood home are motivated by a desire to connect with their past. Seeing the buildings, schools, parks, and playgrounds from their youth helps to establish the psychological and emotional link between the child in the black-and-white photographs and the person they are today. Many people use the trip to get in touch with the values and principles they were taught as children, often as a means to get their lives back on track. Others use that journey to strengthen emotional bonds between themselves and loved ones. Still others return to former homes to work through psychological issues left over from sad or traumatic childhoods. No matter the reason, there are few experiences in one's life that can move a person as deeply and unpredictably as returning home.